PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN UNDERWARE GT MAN PADA PT RICKY PUTRA GLOBALINDO TBK - Monalisa Rosana Hutapea; Awaludin awaludin; rosniwaty Br Bangun; Mella Yunita (VALUE, 2021)
In this era of pandemic and economic crisis, companies must be smart in marketing their products. Tight competition forces companies to innovate and minimize operational costs in order to remain afloat. This research is a descriptive study where the sample in this study was 79 people who were taken by random sampling using a questionnaire, with data analysis techniques including data quality tests, classical assumption tests, multiple regression tests, and hypothesis testing. The results of this study indicate that brand image partially does not have a significant effect on purchasing decisions, this is probably caused by a shift in people's thinking patterns that prioritize quality over brands amid weakening economic conditions this year, while product quality partially has a significant effect on purchase satisfaction. However, Simultaneously Brand image and product quality have a significant effect on purchasing decisions.